Padlet for Learning EFL Speaking: A Technology Review - Maria Stephanie Rahardjo; Titis Maulidiati; Stephannie D.F. Maay; Azhar Arif Darmawan; Elisa Oliveira Fernandes Xavier (E-Link Journal, 2026)
A gradual shift in language learning toward its communicative purpose has put productive skills, such as speaking, in the spotlight. In fact, developing speaking skills is challenging for foreign-language learners due to the interplay of affective, linguistic, and sociocultural factors throughout the process. The recent innovation of a collaborative online board, Padlet, has successfully accommodated learners’ needs for affection, linguistic support, and interaction in developing speaking skills. While prior research predominantly focused on students’ perspectives on using Padlet, this study employs the technology review genre to examine the application itself and critically evaluate the potential benefits and challenges of Padlet for second-language speaking-skill learning, framed within the language-learning principles of Egbert and Shahrokni (2018). Adapting the technology-in-depth exploration approach proposed by Kritandani et al. (2024), the authors present a systematic and credible evaluation.  The study results showed that Padlet has the potential to provide comprehensible input, support language output, facilitate learners’ noticing, increase social interaction, and provide immediate input. Apart from the benefits, the potential challenges in its integration include low internet connectivity in certain rural areas, the ambiguity of picture search, and learners’ uneasiness about both recording themselves and receiving feedback in public. For optimal use, learners should build trusting relationships within their learning community, which may enable them to participate actively in online speaking activities. For beginner learners, the presence of trained instructors may help prevent exposure to unrelated content. It is also advisable for learners to watch the tutorial videos provided by the platform beforehand.